The Role of Vaccination Programs in Reducing Infant Mortality: A Review - Javeed, Asif; Shoaib Rasool, Muhammad; Durrani, Hameed Mumtaz; Naeem, Muhammad; Tariq, Muntaha; Farrukh, Ghazal (Journal of Neonatal Surgery, 2025)
Background: Recently, Pakistan has had high neonatal and child mortality rates, a problem for many developing nations. We found many causes of these rates in our narrative assessment of comprehensive evidence. These include preterm births, birth deformities, poor immunization, hazardous deliveries, inadequate breastfeeding, delivery complications, SIDS, low socioeconomic conditions, and a failing healthcare system. Objective: We aimed to generate practical suggestions for lowering the newborn tetanus incidence in Pakistan by reviewing measures that have significantly reduced the infant death rate in LMICs caused by neonatal tetanus. Methods: In order to find effective therapies for lowering infant mortality due to tetanus, we searched the published literature in the Pubmed and Pubget databases. After deleting redundant material, ten out of twenty studies were selected for preliminary screening. Results: The following interventions were found to be effective in reducing neonatal mortality in low- and middle-income countries: a) vaccinating all pregnant women (married or not) against tetanus toxoid; b) community-based interventions, such as vaccinating all mothers; providing clean and skilled care during delivery; resuscitating newborns; promoting exclusive breastfeeding; cleaning and disinfecting the umbilical cord; and managing infections in newborns. c) Additional vaccinations (on top of the standard EPI program) d) safer methods of administration. Conclusion: Vaccinating pregnant moms is the most effective method for reducing the fatality rate from newborn tetanus. Along with the "high-risk" strategy, clean deliveries, frequent effective prenatal visits, and this one step, resource-poor nations like Pakistan can minimize neonatal tetanus